Incremental Costs in Giant Cell Arteritis. Issue 7 (23rd April 2018) - Mounié, Michael; Costa, Nadège; Sailler, Laurent; Lapeyre‐Mestre, Maryse; Bourrel, Robert; Savy, Nicolas; Molinier, Laurent; Pugnet, Grégory
Abstract : Objective: To assess and compare direct costs between giant cell arteritis (GCA) patients and matched controls and to identify incremental cost drivers. Methods: We carried out a population‐based, retrospective cohort study using the French National Health Insurance System database. Cost analysis was performed from the French health insurance perspective and took into account direct medical and nonmedical costs (2014, €). Costs were evaluated according to different cost components and divided into periods of 6 months for the accurate assessment of care consumption. Longitudinal multivariate regression analyses using generalized estimating equations were used to adjust the effect of GCA on the mean cost over time. Results: Analyses were performed on 96 incident GCA patients and 563 matched controls. The cumulative incremental cost due to GCA was €6, 406 and €7, 236 for 3 and 5 years, respectively. Total incremental costs were significant for the first 18 months, amounting to €1, 342 for the first 6 months, €1, 498 between 6 and 12 months, and €1, 165 between 12 and 18 months ( P = 0.012, P = 0.065, and P = 0.029, respectively). The most important cost drivers were paramedical procedures, inpatient stays, medication, and medical procedures. Multivariate analysis shows the significant effect of GCA on mean cost during the first 3 years of followup (relative risk [RR] 1.72 [95% confidence interval (95% CI) 1.31–2.27], P < 0.001) with significant cost reductions (RR 0.70 [95% CI 0.49–0.99], P = 0.05) at the end of followup. Conclusion: This study provides an accurate assessment of GCA costs during a 5‐year period and gives useful information for future cost‐effectiveness studies based on new expensive biotherapies.